Simple method devised for rapid isolation and identification of Vibrio cholerae from water resources of Sunsari District, Nepal - Shrestha, Bijay Kumar; Shakya, Jenish (Nepal Journal of Biotechnology, 2021)
Cholera is a gastrointestinal disease caused by pathogenic strain of Vibrio cholerae, the disease clinically manifested by rice-water diarrhea, nausea and vomiting. This study aimed to study the incidence of Vibrio species and employ simple method for rapid detection of Vibrio cholerae from water samples of Sunsari, Nepal. Identification of V. cholerae through biochemical tests requires extensive labor and costs. In resource limited laboratories, isolation and identification of V. cholerae often becomes difficult. Therefore, this study also aimed for selecting scope of this methodology as a scientific outcome for rapid isolation and identification of Vibrio cholerae. A total of 100 water samples were collected from Sunsari district in which 25 samples were collected from sewage, 25 from pond, 25 from tap and 25 from tube well. The samples of collected water were sent to the microbiology laboratory of Central Campus of Technology maintained in ice cold box and were enriched in Alkaline Peptone water and selectively isolated from TCBS agar and NA agar without NaCl. Pathogens were isolated and identified by conventional microbiological techniques. Out of 100 water samples collected, sucrose fermenting Vibrio species were isolated only from 16 water samples. Further the selective isolation of V. cholerae from nutrient agar without NaCl isolated 6 isolates from sewage samples and 3 isolates from pond samples. The distribution of Vibrio cholera in the water sample was found to be 9%, distribution of V. alginolyticus was found to be 4% and distribution of V. fluvialis was found to be 3%. In this study, non-sucrose fermenting Vibrio species were not isolated from the water samples. However, sucrose fermenting Vibrio species was obtained with yellow pigmentation in TCBS agar medium. The yellow pigmented colonies of Vibrio isolates recovered from TCBS and even from Nutrient Agar devoid of sodium chloride provided sufficient evidence of V. cholerae after series of other biochemical tests. This study concludes that yellow colonies (sucrose-fermenting) of Vibrio from TCBS agar medium that can grow on nutrient agar without added NaCl and which exhibit a positive oxidase reaction can be confidently identified as presumptive V. cholerae. In resource-constrained environments, this simple method can reduce the labor cost, chemicals and time-consuming procedure of performing multiple biochemical and molecular assays for identification.